The social mysteries of the superior temporal sulcus - Beauchamp, Michael S. (Trends Cogn Sci, 2015)
The superior temporal sulcus (STS) is implicated in a variety of social processes, ranging from language perception to simulating the mental processes of others (theory of mind). In a new study, Deen and colleagues use fMRI to show a regular anterior-to-posterior organization in the STS for different social tasks.